СОВРЕМЕННЫЕ ПОДХОДЫ К ТЕРАПИИ ЗАТЯЖНЫХ И ОСЛОЖНЕННЫХБРОНХОЛЕГОЧНЫХ ЗАБОЛЕВАНИЙ У ДЕТЕЙ («Наука и здравоохранение», 2026)
СОВРЕМЕННЫЕ ПОДХОДЫ К ТЕРАПИИ ЗАТЯЖНЫХ И ОСЛОЖНЕННЫХБРОНХОЛЕГОЧНЫХ ЗАБОЛЕВАНИЙ У ДЕТЕЙ